Optimism and the Psychological Recovery Process Among Informal Caregivers of Inpatients Suffering From Depressive Disorder: A Descriptive Exploratory Study - Coloni-Terrapon, Claire; Favrod, Jérôme; Clément-Perritaz, Aurélie; Gothuey, Isabelle; Rexhaj, Shyhrete (Frontiers in Psychiatry, 2020)
Background: Informal caregivers of people suffering from depressive disorders go through a psychological recovery process. This process is dynamic, deep, catalysed by hope and optimism and characterized by stages from which specific needs ensue. This study aimed to describe the stages of the psychological recovery process and the level of optimism among informal caregivers of psychiatric inpatients suffering from depressive disorders in order to provide adapted nursing support and psychoeducation and facilitate a patient’s own recovery. Methods: A descriptive exploratory study was conducted using a convenience sample of 29 informal caregivers. Participants filled out a sociodemographic questionnaire, a specially adapted Stages of Recovery Instrument (STORI) and the Life Orientation Test–Revised (LOT–R). Results: A mean optimism score of 16.41 showed that informal caregivers are close to the level of the general European population. The sample included all the stages of the recovery process, with 34.5% of participants being in the growth stage. Informal caregivers’ stages in the recovery process were negatively associated with the patient’s length of illness (Rho=-.683, p=.000) and positively associated with the caregivers’ level of optimism (Rho=.564, p=.001). Conclusion: During the inpatient treatment of a close relative suffering from a depressive disorder, informal caregivers go through an individual psychological recovery process involving several stages. In addition to caring for inpatients, nurses are encouraged to meet and support caregivers as soon as possible in their individual recovery process. Furthermore, the development of a suitably adapted clinical tool would facilitate the assessment of the informal caregiver’s stage in the recovery process within care units. A multidisciplinary approach is needed in this domain